Advances in mergers and acquisitions - Finkelstein, Sydney; Cooper, Cary L. (Advances in mergers and acquisitions, 2024)
Advances in Mergers and Acquisitions stands out from the competition due to its focus on three key characteristics: studies from scholars in different countries, with different research questions, relying on different theoretical perspective. Such a broad and inclusive approach to mergers and acquisitions is not easily replicated in academic journals, with much narrower mandates and metrics. Volume 23 of this annual series explores a range of issues, from cross-border mergers and acquisitions, MNE strategies and multi-business firms to outsourcing and strategic choices. This collection of new and current research highlights interesting behavioural themes as well as timely practical solutions to the dilemma of mergers and acquisitions failures. Advances in Mergers and Acquisitions Volume 22 is of interest to scholars in strategic management, organizational theory and behaviour who are studying questions around mergers and acquisitions. Doctoral students will benefit from access to the diversity of research that can trigger new research questions and expanded research agendas.